The numerical models of the estimation of the electrooptical parameters of GaAs - Pincevičius, Albertas; Rakauskas, Rimantas-Jonas; Vošterienė, Svajonė (Lietuvos matematikos rinkinys, 2002)
In this paper we offer method for estimation of the relaxation of a photoconductivity of high resistivity crystal, stimulate by laser impulse. The system of the six nonlinear ordinary differential equations is solved. The relaxation of electrons across four most influential deep levels is taken into account. Electron concentration changes on fifteen orders in a narrow boundary layer (0–5 × 10-8 s). In the sequent layers change of the electrons concentration is slower in the time interval up to 10-4 second. The system of the differential equations was solved by a method Gear with a modification of a step. The electro-optical parameters of the crystal we found out by the comparison of calculation and experiment outcomes. From the other side it is possible to use calculation for improvement of the characteristics of the devices.